Analysis and design of axial flux permanent magnet wind generator system for direct battery charging applications - Rossouw, Francois Gerhardus (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.